LockED: Uma Ferramenta para o Controle de Alterações no Desenvolvimento Distribuído de Artefatos de Software - Teixeira, Hugo Vidal; Murta, Leonardo Gresta Paulino; Werner, Cláudia Maria Lima (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2001: Anais do XV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2001.24006, 2001)
This work describes an approach to support change control in distributed development of software projects. This approach differs from existing ones because it does not only handle source code, but also other artifacts produced within other stages of the software development process. The proposed approach uses Internet resources for communication and exchange of artifacts among the developers and the server.